2000
DOI: 10.1002/1099-0712(200003/04)10:2<81::aid-amo407>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the surface morphology and structure and the photoluminescence of amorphous PbTiO3 thin films obtained by the chemical route

Abstract: A polymeric precursor method was used to synthesis PbTiO 3 amorphous thin film processed at low temperature. The luminescence spectra of PbTiO 3 amorphous thin films at room temperature revealed an intense single-emission band in the visible region. The visible emission band was found to be dependent on the thermal treatment history. Photoluminescence properties versus different annealing temperatures were investigated. The experimental results (XRD, AFM, PL) indicate that the nature of photoluminescence (PL) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
7

Year Published

2003
2003
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 11 publications
1
17
0
7
Order By: Relevance
“…5 ilustram que os dados são consistentes com a interpretação da absorbância óptica, ou seja, o "gap" visível da banda é controlado pelo grau de desordem estrutural e térmica da amostra do CW. Neste trabalho, o modelo está baseado na transferência de elétrons dos oxigênios para os íons W 4+ [12,13]. Assim sendo, os resultados obtidos nos cálculos teóricos indicam que na formação do "cluster" amorfo, por intermédio da deformação da ligação do oxigênio O(18), há introdução de níveis eletrônicos delocalizados na região entre a banda de valência e de condução.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…5 ilustram que os dados são consistentes com a interpretação da absorbância óptica, ou seja, o "gap" visível da banda é controlado pelo grau de desordem estrutural e térmica da amostra do CW. Neste trabalho, o modelo está baseado na transferência de elétrons dos oxigênios para os íons W 4+ [12,13]. Assim sendo, os resultados obtidos nos cálculos teóricos indicam que na formação do "cluster" amorfo, por intermédio da deformação da ligação do oxigênio O(18), há introdução de níveis eletrônicos delocalizados na região entre a banda de valência e de condução.…”
Section: Resultsunclassified
“…Materiais com estas características ópticas podem apresentar estas propriedades FL [10,11]. Como no caso dos tungstatos amorfos, várias propriedades interessantes de perovsquitas têm sido relatadas, inclusive mostrando que o comprimento de onda emitido está relacionado ao comprimento de onda incidente [12][13][14][15][16].…”
Section: Introductionunclassified
“…[1][2][3] We have reported several interesting properties of these amorphous titanates, including the fact that the PL emission wavelength depends on the exciting wavelength, suggesting electronic transitions between a distribution of vibronic states 4 and that the PL phenomena are related to the amorphous state. 2,5 These studies revealed important aspects. First, a simple water-based chemical process was used, allowing amorphous titanates to be processed at temperatures as low as 523 K in the form of thin films or particles.…”
Section: Introductionmentioning
confidence: 99%
“…Por sua vez, o fenômeno da fotoluminescência em titanatos amorfos, à temperatura ambiente, ainda não foi completamente modelado. Várias propriedades destes titanatos amorfos têm sido descritas, inclusive o fato que as emissões de ondas fotoluminescentes estão relacionados ao comprimento de onda de excitação e que os fenômenos fotoluminescentes estão relacionados ao estado amorfo [15,16].…”
Section: Fotoluminescência Em óXidos Amorfosunclassified